Interaksi Sosial Dan Komunikasi Interpersonal Penerima Pkh Di Bank Sampah Kreatif Berseri Kelurahan Lempuing - Ledyawati (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the social interaction and interpersonal communication patterns of mothers receiving the Family Hope Program (PKH) at the Creative Berseri Waste Bank in Lempuing Village, and to understand how these interactions and communications shape social capital, identity construction, and power dynamics within the community. The research method used is a qualitative approach with a descriptive interpretive research type. Data collection techniques include participant observation, in-depth interviews, and documentation. Informants were selected using purposive sampling consisting of waste bank administrators and members with varying levels of involvement. Data analysis uses the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions with verification. The results of the study indicate that social interactions in the waste bank are manifested in associative forms including cooperation, accommodation, and assimilation that create mechanical solidarity based on collective awareness as fellow PKH recipients.but also creates a peaceful and prosperous society. Behind the seemingly egalitarian communication lies a power dynamic at work through disciplinary power and governmentality, where members voluntarily discipline themselves according to standards of economic efficiency. Waste banks create a new social structure with stratification based on a combination of economic dimensions, social status, and organizational power, and provide a mechanism for achievement-based vertical social mobility, albeit limited to the micro-community scale.